Long-Term Mental Health Among Low-Income, Minority Women Following Exposure to Multiple Natural Disasters in Early and Late Adolescence Compared to Adulthood - Jacobs, Marni B. (Child Youth Care Forum, 2015)
BACKGROUND: High impact experiences following a natural disaster have been shown to influence later psychopathology. Individual-level factors such as age may also contribute to a disaster’s impact on mental health, though it is unclear whether young age confers a protective effect or represents a period of increased risk as compared to adulthood. OBJECTIVE: The present study evaluated the influence of adolescent age and hurricane experiences on mental health in the years following multiple hurricanes in the New Orleans region. METHODS: 794 women, currently aged 18–45, participating in a cohort study of lifetime adversity and reproductive health completed a survey about hurricane experience and current mental health. Joint associations between disaster experience and age at the time of disaster on depression and post-traumatic stress disorder (PTSD) were evaluated. RESULTS: Compared to women who were adults at the time of the disaster, being in early adolescence resulted in reduced depression and PTSD up to 9-years post-disaster, controlling for hurricane experiences, time since disaster, and income. A similar effect was not observed among older adolescents. Increased endorsement of feeling one’s life was in danger and experiencing illness or injury resulted in increased odds of depression, while danger was associated with increased odds of PTSD. CONCLUSIONS: Younger age at the time of a natural disaster may confer a protective effect on mental health outcomes post-disaster, even when disaster experiences are considered, potentially representing the importance of parental support and cognitive development on disaster effects.